'Soft ways of doing hard things': women mediators and the question of gender in mediation. (1st October 2020) - Turner, Catherine
ABSTRACT: Arguments in favour of increasing the number of women mediators rest on existing research in the field of Women Peace and Security that suggests that where women are included in peace processes that they create more sustainable agreements. It is often suggested that women mediators will bring different- 'soft'- skills to mediation and that they will be catalysts to women's empowerment. Drawing on a series of interviews with women mediators in Northern Ireland the article does two things. First, it explores the skills that women felt they brought to their work, and second, it draws out the relationship between mediation and gender as perceived by the participants. What the results demonstrate is that while participants did not consider it the role of a mediator to advance a particular normative agenda through their work, this did not translate into a gender blind approach in practice.